2015
DOI: 10.1530/ec-15-0041
|View full text |Cite
|
Sign up to set email alerts
|

Short telomere length is associated with arterial aging in patients with type 2 diabetes mellitus

Abstract: It is known that glucose disturbances contribute to micro- and macrovascular complications and vascular aging. Telomere length is considered to be a cellular aging biomarker. It is important to determine the telomere length role in vascular structural and functional changes in patients with diabetes mellitus. We conducted a cross-sectional observational study in a high-risk population from Moscow, Russia. The study included 50 patients with diabetes and without clinical cardiovascular disease and 49 control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Unfortunately, these studies do not give results of a similar evaluation for 2 h OGTT levels. 22,23 It is surprising that although the association between IGT and LTL shortening was revealed a long time ago, epidemiological studies of correlational association between LTL and distinctly FPG and 2 h OGTT levels such as ours seem to not have been previously performed. Greek researchers reported 24 that significant telomerase activity was detected in circulating peripheral blood mononuclear cells in persons with metabolic syndrome (a cluster of cardiovascular and pro-thrombotic risk factors, such as insulin resistance, impaired glucose tolerance, dyslipidemia, obesity, and elevated blood pressure), which may partially explain the absence of association between several indicators of insulin resistance (FPG and LTL) that we have revealed.…”
Section: Discussionmentioning
confidence: 79%
“…Unfortunately, these studies do not give results of a similar evaluation for 2 h OGTT levels. 22,23 It is surprising that although the association between IGT and LTL shortening was revealed a long time ago, epidemiological studies of correlational association between LTL and distinctly FPG and 2 h OGTT levels such as ours seem to not have been previously performed. Greek researchers reported 24 that significant telomerase activity was detected in circulating peripheral blood mononuclear cells in persons with metabolic syndrome (a cluster of cardiovascular and pro-thrombotic risk factors, such as insulin resistance, impaired glucose tolerance, dyslipidemia, obesity, and elevated blood pressure), which may partially explain the absence of association between several indicators of insulin resistance (FPG and LTL) that we have revealed.…”
Section: Discussionmentioning
confidence: 79%
“…Many of these have attempted to understand the role of telomeres in human cancer 14 15 , hypertension and atherosclerosis 16 . Recently, it was shown that patients with diabetes had more dramatic vascular changes in comparison to the control group resulting in shorter telomeres 17 . Keeping all this in mind we hypothesized that there may be a connection between telomere length and diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…LTL is significantly shorter in T2DM patients compared with controls over a wide age range and is significantly associated with the presence and number of diabetes complications [ 65 ]. Finally, a strong association has been highlighted between telomere length and the presence of some diabetes complications and general arterial aging [ 66 , 67 ].…”
Section: Sasp Inflammaging and Type 2 Diabetesmentioning
confidence: 99%